Surface characterization and Remazol Red adsorption by asymmetric polyethersulfone membranes modified by polyelectrolyte complexes - da Silva Vale, Rayane; Bezerra da Silva, Vanessa; Marcio Paranhos, Caio; Contiero, Jonas [UNESP]; Knauss, Daniel M. (Wiley, 2024)
Polyethersulfone (PES) membranes containing 4-fluorophenyl sulfone-terminated poly(diallylpiperidinium hexafluorophosphate)-sulfonated poly(ethylene terephthalate) polyelectrolyte complexes (PECs) were obtained via phase inversion using three different methods that enabled the complexation of polyelectrolytes (PELs) to occur before, after, and during membrane formation. Atomic force microscopy-infrared spectroscopy analysis revealed varying concentrations of the polyanion depending on the preparation method and confirmed the presence of PECs in the membranes, highlighting an increase in surface roughness. Zeta potential measurements demonstrated positive surface charges for the membrane comprising PES and the polycation. The reduction in zeta potential in PEC membranes corresponded with the neutralization of positive groups by sulfonated poly(ethylene terephthalate. Scanning electron microscopy micrographs depicted surface imperfections in PEC membranes, emphasizing the influence of PECs on membrane surfaces. The water contact angle decreased, indicating increased hydrophilicity in PEC membranes. Additionally, dye adsorption results showcased significant adsorption, with the membranes absorbing at least 60% of Remazol Red from an aqueous solution. Notably, the Blend membrane outperformed others, exhibiting an exceptional adsorption rate exceeding 92%.
Keywords: phase inversion; poly (diallyl piperidinium); polymeric membranes; sulfonated poly (ethylene terephthalate)